Quality of work life among primary health care nurses in the Jazan region, Saudi Arabia: a cross-sectional study - Almalki Mohammed J; FitzGerald Gerry; Clark Michele (BMC, 2012)
Abstract Background Quality of work life (QWL) is defined as the extent to which an employee is satisfied with personal and working needs through participating in the workplace while achieving the goals of the organization. QWL has been found to influence the commitment and productivity of employees in health care organizations, as well as in other industries. However, reliable information on the QWL of primary health care (PHC) nurses is limited. The purpose of this study was to assess the QWL among PHC nurses in the Jazan region, Saudi Arabia. Methods A descriptive research design, namely a cross-sectional survey, was used in this study. Data were collected using Brooks' survey of quality of nursing work life and demographic questions. A convenience sample was recruited from 134 PHC centres in Jazan, Saudi Arabia. The Jazan region is located in the southern part of Saudi Arabia. A response rate of 91% (n = 532/585) was achieved (effective response rate = 87%, n = 508). Data analysis consisted of descriptive statistics, t-test and one way-analysis of variance. Total scores and subscores for QWL items and item summary statistics were computed and reported using SPSS version 17 for Windows. Results Findings suggested that the respondents were dissatisfied with their work life. The major influencing factors were unsuitable working hours, lack of facilities for nurses, inability to balance work with family needs, inadequacy of vacations time for nurses and their families, poor staffing, management and supervision practices, lack of professional development opportunities, and an inappropriate working environment in terms of the level of security, patient care supplies and equipment, and recreation facilities (break-area). Other essential factors include the community's view of nursing and an inadequate salary. More positively, the majority of nurses were satisfied with their co-workers, satisfied to be nurses and had a sense of belonging in their workplaces. Significant differences were found according to gender, age, marital status, dependent children, dependent adults, nationality, nursing tenure, organizational tenure, positional tenure, and payment per month. No significant differences were found according to education level of PHC nurses and location of PHC. Conclusions These findings can be used by PHC managers and policy makers for developing and appropriately implementing successful plans to improve the QWL. This will help to enhance the home and work environments, improve individual and organization performance and increase the commitment of nurses.